种仿生催化氧化制备二苯甲酮的方法 (2017)
本发明公开了种仿生催化氧化制备二苯甲酮的方法。该方法以二苯甲烷为原料，以金属卟啉化合物为催化剂，以叔丁基过氧化氢、间氯过氧苯甲酸或双氧水为氧化剂，控制在反应温度为40~100℃的条件下进行催化反应得到二苯甲酮。本发明与其他工艺相比具有反应条件温和、催化效果好、产物选择性高、工艺简单等优点。 The invention discloses a method for preparing benzophenone through biomimetic catalytic oxidation, which takes diphenylmethane as a raw material, takes a metalloporphyrin compound as a catalyst, and takes tert-butyl hydroperoxide and metachloroperbenzoic acid or hydrogen peroxide as a oxidizing agent, and benzophenone can be obtained through catalytic reaction by controlling the reaction temperature at 40-100 DEG C. The method has the advantages of mild reaction condition, good catalysis effect, high products selectivity and simple process.